ACCURACY OF ULTRASOUND IN DETECTION OF ANTERIOR CRUCIATE LIGAMENT TEAR OF KNEE IN CCOMPAISON TO MAGNETIC RESONANCE IMAGING - Adil Qayyum (Army Medical College Rawalpindi, 2019)
Objective: To determine the accuracy of ultrasound in detection of anterior cruciate ligament injury.